Applications of the Axiom of Choice to Constructions in Euclidean Spaces - Komjáth, Péter (Sarajevo Journal of Mathematics, 2022)
We give a short account of corollaries of the Axiom of Choice, which show the existence of curious configurations or colorings of the Euclidean spaces. The paper is readable even with a minimal knowledge of set theory. A possible new result is also proved: pairwise disjoint flags can be elected on each point of the plane.